Preliminary Phytochemical Screening of Moringa Leaves (Moringa oleifera): An Ethnomedicinal Investigation in Kaway XVI, West Aceh - Irzal Fanany; Nasrianti Syam; Cukri Rahma; Laila Apriani Hasanah Harahap; Ravi Masitah; Rubi Rimonda; Mardi Fadillah (Universitas Labuhanbatu, 2026)
Background: Moringa oleifera Lam. represents a crucial botanical asset globally, yet its localized phytochemical expressions under specific coastal microclimates remain under-explored, threatening the standardization of community-based traditional medicine. M. oleifera Lam. is a versatile, multipurpose tree species that holds significant importance in the ethnomedicine of the West Aceh community. While previous studies heavily rely on dried extracts, this study establishes the baseline phytochemical integrity of fresh, unextracted coastal specimens, bridging the gap between empirical local preparation methods and laboratory validation. This study aimed to characterize the qualitative phytochemical profile of M. oleifera leaves sourced from Kaway XVI Subdistrict and to document their traditional applications as a basis for scientific validation. Methodology: Employing a qualitative experimental, phytochemical screening was performed directly on fresh leaf samples using standardized assays-including Mayer’s, Wagner’s, and Dragendorff’s tests for alkaloids, the Shinoda test for flavonoids, and the ferric chloride test for phenolics—thereby minimizing the degradation of secondary metabolites often associated with intensive solvent extraction processes. Findings: The qualitative analysis revealed the presence of alkaloids, flavonoids, phenolic compounds, saponins, tannins, and steroids, while terpenoids were notably absent. The identification of these bioactive constituents provides scientific substantiation for the local ethnomedicinal use of M. oleifera as both a nutritional supplement and a galactagogue agent. This study provides a baseline phytochemical profile derived from fresh, non-extracted plant material, offering a more ecologically relevant representation of bioactive compounds as utilized in traditional practices. Contribution: The findings contribute to bridging the gap between empirical ethnomedicine and laboratory validation, and support the standardization of Moringa as material for nutraceutical, and functional food development